Legal Certainty For Holders of Land Rights Over The Issuance of Multiple Certificates - Iskandar Soewito, Rizal; Djajaputra, Gunawan (Journal of Law, Politic and Humanities, 2024)
One of the fundamental principles of the rule of law is the guarantee of legal certainty and legal protection of the rights of citizens. Laws and regulations in Indonesia, including the 1945 Constitution and Government Regulations, emphasize the state's interest in regulating the use and utilization of natural resources, including land, for the public interest and prosperity of the people. However, land is often a source of complex disputes because of its limited quantity and importance for human life. Land registration or land registration is an important step in providing legal certainty regarding land ownership. Through regulations, the government determines procedures and procedures for carrying out land registration, including collecting physical and juridical data and issuing land title certificates. However, there are still challenges and obstacles in implementing land registration, including the issuance of multiple certificates. Internal and external factors such as maladministration, lack of public knowledge, and the high rate of development can cause the issuance of double certificates. Legal protection is needed to ensure legal certainty for owners of land rights, including in resolving multiple certificates through a fair and just legal process. Regulations regarding land registration and land rights certificates also provide a time limit for parties who feel they have rights to land to submit objections, thus providing legal certainty for land rights holders. Land certificates play a dual role as a State Administrative Decree (KTUN) and proof of civil rights to land, so that the resolution of disputes regarding land certificates can be carried out through two different judicial channels.